Managing the nursing shortage during the Covid-19 pandemic: A qualitative study - Rr Tutik Sri Hariyati; Hanny Handiyani; Erwin Erwin; Sri Widawati; Welas Riyanto; Rita Herawati; Patricia S Lasmani; I Gusti A. Nyoman (Wolters Kluwer Medknow Publications, 2023)
Background: Nursing care contributes to the safety and the quality of care of patients. During the COVID-19 pandemic, nurses became frontline care providers. Materials and Methods: A qualitative study was conducted using an online focus group discussion of eight nurse committee members from six hospitals. After the data were collected, the study continued with inductive thematic analysis. The data were organized and extracted to identify meaningful statements and formulate meanings. Inductive thematic analysis was used, resulting in three themes and six subthemes. Results: The themes related to managing the nursing workforce, schedules, rosters, shifts, goals of re-design staffing, and the nurse-patient ratio. Conclusions: The management of the nursing staffing was modified to protect nurses during the COVID-19 pandemic. The nurse manager redesigned workforce planning to ensure a safe environment for nurses.